“The graduates of the Postgraduate Diploma in Community Eye Health: how do they manage?” - Minnies, Deon (Department of Public Health and Family Medicine, 2021)
The Postgraduate Diploma in Community Eye Health (PgDCEH) has been offered at the University of Cape Town, South Africa since 2009 to develop management capacity in support of the delivery of effective and efficient eye care services in sub-Saharan Africa. We investigated how graduates applied the PgDCEH-acquired management competencies and the factors that enabled or constrained them to apply these competencies. A multiple case study design was used, employing mixed methods of data collection and analysis. Data collection comprised of a questionnaire survey, in-depth interviews and review of various supporting documents, including assignments submitted by students. Twenty-six of the 34 students who graduated from 2009 to 2014 submitted completed questionnaires. Of these, 15 purposively selected graduates and their secondary key informants participated in in-depth interviews. We found that the PgDCEH elicited some positive effects on the graduates, especially in their ability to perform management tasks and the level of confidence they have in their abilities. There were some personal achievements, but no significant programme improvements were observed. This study provided evidence that the PgDCEH as a health system strengthening intervention struggled to generate the anticipated response of improved eye care programme performance. Personal motivation, suitability of the training and opportunity to apply were the main factors determining how graduates apply management competencies. The utilization of the project management approach, a greater focus on health system maintenance and attention to the dynamic of change in people's lives are critical determinants of success in eye health programmes. The research also highlighted the importance of health care workers' personal motives and motivations as drivers of success and achievement on programme level, and that line management support, supervision and proper performance management are required to attain this. This research broadened understanding of how PgDCEH graduates interact with their work environment and uncovered ways to improve the design and delivery of management training for eye health workers in the future. Revision of the criteria for selection, strengthening focus on leadership, project and relationship management topics, and integrating the training into health professions' education programmes may substantially improve the impact of health management education. The study concluded that the constituent elements of the health system are not inanimate objects, as commonly portrayed, but people, who are connected in intimate, complex and multi-dimensional ways through communication, relationships and team dynamics to deliver health outcomes.